PERKEMBANGAN LANDASAN YURIDIS SISTEM PENDIDIKAN NASIONAL UNTUK MEWUJUDKAN SUMBER DAYA MANUSIA YANG HANDAL - ARLIMAN S, LAURENSIUS (Ensiklopedia Education Review, 2019)
The independence of the Indonesian people was proclaimed on the date August 17, 1945. The day after that, on the date August 18, 1945 Preparatory Committee for Indonesian Independence (PPKI) establishes the 1945 Constitution as a State constitution. If you examine the fourth paragraph of the Preamble of the 1945 Constitution, there are express and implied national ideals in the field of education, namely to educate the life of the nation. In connection with this, Article 31 paragraph (3) of the 1945 Constitution mandates that "the Government undertakes and organizes a national education system, in order to educate the nation's life, which is regulated by law". The practice of national education is carried out by referring to certain juridical grounds that have been established, both in the form of laws and government regulations regarding education. Educators and education staff need to understand the various juridical foundations of the national education system and make it the starting point for implementing their roles. Thus it is hoped that the orderly implementation of the national education system will be created, which is one of the prerequisites for achieving national education goals Keywords: Development, Juridical, Education, Human Resources.